Critical thinking, creativity, self-efficacy, and teaching practice in Peruvian teacher trainers - Arce-Saavedra, Boris Jesús (2022)
The relationship between dispositions towards critical thinking, creative-innovative performance, self-efficacy and teaching practice was assessed in Peruvian teacher trainers from the Amazonian region of San Martin. Direct and big relationships were found between all variables. A model that explained 42% of the variance of teaching practice is presented, where dispositions towards critical thinking and creative and innovative performance have a direct effect on teacher self-efficacy. In addition, teacher self-efficacy fully mediates the relationship between dispositions toward critical thinking, and partially mediates the relationship between creative-innovative performance and teaching practices. Likewise, results show differences according to sex, work experience, specialization and work place. It is suggested to include other actors to get a holistic view of the teachers’ trainer capacities.